PERFORMANCE APPRAISALS:THE RESEARCH PRACTICE GAP - Asti B Larasati (Buletin Psikologi, 1993)
In their monumnetal book "Passion for Excellence", Tom Peters and Nancy Austin (1985) emphasized the fact that people are key to productivity gains. It Sounds elementary and very basic but in the hustle of everyday life, people too often receive less attention than they should.